Análisis de la situación actual de los Expedientes de Inscripción y Reinscripción de los Productos Farmacéuticos de la DROGUERIA LKM PERU S.A. presentados a DIGEMID, Julio 2010-Diciembre 2014 - Rodriguez Jaramillo, Johanna Mozi (2015)
In Peru, the National Authority of Pharmaceutical Products, Medical Devices and Health Products (ANM) in charge is the Directorate General of Medicines, Supplies and Drugs -DIGEMID, this is responsible for proposing guidelines within their scope regulate, regulate, evaluate and controlling the provisions of Law No. 29459 "Law of Pharmaceutical Products, Medical Devices and Health Products" and related standards. It is therefore responsible for granting the Health Register (RS) which gives the holder the manufacture, import, storage, marketing, distribution, dispensing or use of such products. This report was to carry out an analysis of the current situation of enrollment and school records of Pharmaceutical Products Drugstore LKM PERU SA DIGEMID presented, in July 2010-December 2014 identifying the delay of the final response of the entity under the terms established by product category. For analytical study descriptive, retrospective and cross-sectional technique was used and taken as sources of information the database records registration and re-registration of pharmaceutical products PERU LKM SA Drugs period July 2010 - December 2014 and No. 29459, Law No. 27444, Law DS No. 016-2011-SA and its amendment S.D. No. 016-2013-SA. According to the results, the nomination files to DIGEMID during the period July 2010-December 2014 was obtained from a total of 38 cases, 10 were approved, 5 denied and 23 are still under evaluation and records Reenrollment presented was obtained from a total of 20 records, 7 were approved, 0 refused and 13 are still under evaluation. All approved and denied in both cases had a prior notification records and found that there was a delay in the issuance of the RD / Office of Health Registry by the ANM